Economic rationality and educational realities: efficiency effects of institutional mergers in German adult education (1995–2017) - Echarti, Nicolas [Verfasser]; Reichart, Elisabeth [Verfasser]; Martin, Andreas [Verfasser] (My University, 2024)
„The policy of merging education institutions to improve efficiency and reduce public expenditure has gained popularity in many European countries. However, although this phenomenon is observed in adult education, there is currently a paucity of evidence on the subject within this field. We integrated novel data from 101 mergers of adult education centres in Germany between 1995 and 2017 with longitudinal performance data (n = 21,032) and used Poisson pseudo-marginal-likelihood fixed effects analysis to examine the impact of institutional mergers on funding levels, educational provision, and efficiency. Our results show that those institutions that were involved in a merger experienced significant reductions in institutional funding and hours of educational provision post-merger. However, the effects were smaller when we controlled for organisation-specific trends, suggesting that some of the reductions were a continuation of pre-merger consolidation trends rather than solely due to mergers. In terms of efficiency, positive effects were observed in the short run, but estimates for the medium and long run were relatively small and not statistically significant. Moreover, there was considerable variation in efficiency estimates, highlighting the heterogeneity of outcomes across cases. Thus, our study provides limited evidence to support the hypothesis that the analysed mergers have led to improved efficiency.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.3 Bildungsträger; S 3.3.1 Volkshochschulen; 370; Erwachsenenbildung; Weiterbildungseinrichtung; Volkshochschule; Effizienz; Finanzierung